2010
DOI: 10.1177/0956797610361706
|View full text |Cite
|
Sign up to set email alerts
|

Infection Breeds Reticence

Abstract: Social living brings humans great rewards, but also associated dangers, such as increased risk of infection from others. Although the body's immune system is integral to combating disease, it is physiologically costly. Less costly are evolved mechanisms for promoting avoidance of people who are potentially infectious, such as perceiving oneself as less social and increasing the tendency to make avoidant movements. In Experiment 1, exposure to a disease prime led participants to rate themselves as less extraver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
185
6
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(209 citation statements)
references
References 37 publications
12
185
6
6
Order By: Relevance
“…While it has been suggested that introversion may-via general social reticence-serve a disease-avoidance function (Mortensen et al, 2010;Schaller & Murray, 2008), introversion does not explain the effect of disgust on personal space in this study, which suggests that introversion may be associated with personal space for reasons other than disease avoidance.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…While it has been suggested that introversion may-via general social reticence-serve a disease-avoidance function (Mortensen et al, 2010;Schaller & Murray, 2008), introversion does not explain the effect of disgust on personal space in this study, which suggests that introversion may be associated with personal space for reasons other than disease avoidance.…”
Section: Resultscontrasting
confidence: 45%
“…The behavioral immune system has been implicated in many disease-specific defensive responses (e.g., Mortensen, Becker, Ackerman, Neuberg, & Kenrick, 2010;Park, Schaller, & Crandall, 2007). The most obvious means of avoiding infection is maintaining a physical buffer, to keep sources of infection at a safe distance.…”
Section: Introductionmentioning
confidence: 99%
“…new experiences and new ideas, they more strongly support conformist actions by others, they express greater dislike for non-conformists, and they make harsher moral judgements about people who violate social norms [14,36,45]. There are implications also for conservative political attitudes, which are characterized by attitudinal defence of cultural traditions.…”
Section: (B) Context-contingent Responsesmentioning
confidence: 99%
“…Following experimental manipulations designed to make the threat of infectious disease temporarily salient, people report lower levels of extraversion and also exhibit more avoidant motor responses toward other people [36].…”
Section: (B) Context-contingent Responsesmentioning
confidence: 99%
“…Responding to an aversive feature of the environment, whether it is indicative of a violation of order, purity or security, must ultimately work via a sympathetic nervous system that will prejudice a broad category of action such as avoiding or approaching [26]. Consequently, in addition to recognizing the uniqueness of individual categories of response, many researchers also have found useful a 'biphasic' model which holds that emotion is a product of varying activation of two motivational systems: appetitive and defensive [27,28]. Both of these systems 'are evolutionarily old, shared across mammalian species and have evolved to mediate the behaviours that sustain and protect life' [29, p. 30].…”
Section: Introductionmentioning
confidence: 99%